2004
DOI: 10.1089/1044549041474779
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Resident, Immunoglobulin Joining Chain, Can Be Secreted by Perturbation of the Calcium Concentration in the Endoplasmic Reticulum

Abstract: We established a transient human joining (J)-chain gene expression system in the baby hamster kidney (BHK) cell. The J-chain was detected as a 29-kDa single band on Western blotting. Immunofluorescent staining of the transfectant revealed an exclusive localization of the J-chain in the endoplasmic reticulum (ER). Intracellular transport experiment revealed that incubating conditions favorable for vesicular stomatitis virus glycoprotein (VSV-G) transport did not allow the J-chain to exit from the ER. Analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…For Western blotting, 100 -200 g of total protein was subjected to 10% SDS-PAGE. The separated protein was transferred to an Immobilon membrane (Millipore) electrophoretically, and Western blotting was performed as described previously (Asano et al, 2004). The rabbit anti-TRPV1 antibody (1:200 dilution with 1% bovine serum albumin (BSA)-PBST in 0.1% Tween 20-PBS; Alomone) was used as the primary antibody.…”
Section: Methodsmentioning
confidence: 99%
“…For Western blotting, 100 -200 g of total protein was subjected to 10% SDS-PAGE. The separated protein was transferred to an Immobilon membrane (Millipore) electrophoretically, and Western blotting was performed as described previously (Asano et al, 2004). The rabbit anti-TRPV1 antibody (1:200 dilution with 1% bovine serum albumin (BSA)-PBST in 0.1% Tween 20-PBS; Alomone) was used as the primary antibody.…”
Section: Methodsmentioning
confidence: 99%
“…The cell lysates were cleared by centrifugation, and protein concentration was measured with a Bio-Rad protein assay kit (Tokyo, Japan). A 100 μg sample of total protein was separated using 10% SDS-PAGE, and Western blotting was performed as described previously (15). Briefly, after 1 h of blocking with 1% BSA-PBST (0.1% Tween 20), the membrane was incubated with rabbit anti-mouse TLR 5 antibody (Ab) (×50 diluted with 1% BSA-PBST) (Santa Cruz, CA, USA) or with rabbit anti-mouse glyceraldehyde-3-phosphate dehydrogenase (GAPDH) Ab (×1,000 diluted with 1% BSA-PBST) (Chemicon, Tokyo, Japan) for 1 h at room temperature (RT).…”
Section: Western Blottingmentioning
confidence: 99%
“…Morphological analysis of VSV-G intracellular transport was performed as previously described (4). BHK cells were plated on coverslips and transfected with a pET11d-GFP-tsO45.…”
Section: Morphological Analysis Of Transportmentioning
confidence: 99%
“…Drainage of calcium ions from the ER by calcium ionophores can cause rapid secretion of ER-resident proteins (2,3). A previous report found that the ER-resident protein immunoglobulin joining chain (J-chain) was released from ER-retention mechanisms and secreted outside cells by incubating J-chain-transfected fibroblasts with the calcium ionophore ionomycin (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation